The role of the construction sector - Martina Kirchberger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The construction sector plays a key role in providing structures for economies. This paper surveys the literature on key issues pertaining to the construction sector. It starts by summarizing our knowledge about differences in unit costs across time and space. It then discusses key bottlenecks in the sector related to organization and capabilities, institutional constraints, critical inputs, and governance and corruption. It concludes by outlining policy options related to institutional and regulatory reforms as well as procurement and local content.
Keywords: O18; L74; H54; H57; 330; construction; infrastructure; procurement; unit costs